JEMEK SUPARDI, MIME ARTIST INDONESIA (A Study of Life History) - Indar Sabri; Muhammad Jazuli; Totok Sumaryanto; Autar Abdillah (Humanus: Jurnal Ilmiah Ilmu-ilmu Humaniora, 2019)
This study aims to examine the biography of pantomime figures named  Jemek Supardi, who is known as the maestro of Indonesian pantomime, which includes: life history, way of thinking and his roles in developing pantomime in Indonesia. This study uses biographical theory, by telling the life of a character. This study also uses some supporting theories: life history theory, creativity theory, and role theory. This research is a qualitative research with a biographical study approach to describe the history of one's life (life history). Data collection techniques are carried out by observation, interviews and documentation. Jemek Supardi Supardi's research as subject of study. Data analysis by arranging, sorting, categorizing and grouping the results of observations, interviews, and documentation studies that have been collected. Data analysis is process by reducing the data become a logical and systematic the description. The results and the discussions from The Background of  Jemek Supardi Life History is a tenacious person who dares to try new things. Flowing movement is the initial capital in practicing pantomime. His family and environment made Jemek Supardi confident in his abilities. Emotional memories, internal press creativity and external press creativity were the foundation thinking of  Jemek Supardi. Jemek Supardiworks as an artist and resource person is a manifestation of his role in the existence of mime in Indonesia.Keywords: Jemek Supardi, Pantomime, Life History.JEMEK SUPARDI, MIME ARTIST INDONESIA (Sebuah Kajian Sejarah Hidup)Penelitian ini bertujuan mengkaji biografi tokoh pantomime bernama Jemek Supardi yang dikenal sebagai maestro pantomim Indonesia, yang meliputi: sejarah hidup, pemikiran dan peran dalam mengembangkan pantomim di Indonesia. Penelitian ini menggunakan teori biografikal  yaitu penceritaan tentang kehidupan tokoh.   Penelitian ini juga menggunakan teori pendukung yaitu:  teori sejarah hidup, teori kreativitas,  teori peran.  Penelitian ini merupakan penelitian kualitatif dengan pendekatan studi biografikal untuk memaparkan tentang sejarah hidup seseorang (life history).  Teknik pengumpulan data dilakukan dengan cara observasi, wawancara dan dokumentasi. Subjek penelitian Jemek Supardi. Analisis data dengan cara mengatur, mengurutkan,  mengkategorikan serta mengelompokkan hasil observasi, wawancara, dan studi dokumentasi yang telah terkumpul.  Analisis data dengan mereduksi kumpulan data  menjadi perwujudandeskripsi yang logis dan sistematis.  Hasil dan pembahasan Latar belakang Sejarah Hidup Jemek Supardi merupakan peribadi yang ulet dan berani mencoba hal baru. Gerakan mengalir adalah modal awal dalam berlatih pantomim.  Keluarga dan lingkungannya membuat Jemek Supardi yakin dengan kemampuannya.  Ingatan emosi, kreativitas internal press dan kreativitas external press  menjadi landasan pola piker Jemek Supardi.  Jemek Supardi berkarya sebagai seorang seniman dan narasumber merupakan wujud peranya dalam eksistensi pantomim di Indonesia.Kata Kunci: Jemek Supardi Supardi, Pantomim, Life History.